Selective Catalytic Oxidation of Organic Sulfides to Sulfoxides without Forming Sulfones over Solid Molybdenum Blue: Kinetic and Thermodynamic Studies - Ratheshkumar, P.; Induja, S.; Raghavan, P.S. (Asian Journal of Chemistry, 2020)
The present investigation reports studies on the selective catalytic oxidation of organic sulfide substrates over molybdenum blue catalyst supported on boron phosphate. The catalyst was synthesized through partial precipitation method and characterized by XRD, FTIR and SEM techniques. The sulfoxidation was carried out in a batch reactor using benzyl phenyl sulfide as the substrate over the present catalyst and the reaction parameters were varied and optimized. The results were compared with the MoO3 impregnated boron phosphate. The catalyst was also studied for its performance over other sulfide substrates and the results were compared with available studies in literature. The reaction followed pseudo first-order kinetics and rate of the reaction under optimized condition was 10.1 × 10-3 min-1, with energy of activation of 29.3 kJ/mol. The Mo-O-Mo bridging and -Mo=O bonds present in molybdenum blue were participating in the reaction and possible mechanism has been proposed. The 100% selectivity of the product towards sulfoxide has been attributed to the big-wheel structure of molybdenum blue as it sterically hinders further reaction of sulfoxides formed to sulfones.